Identification and gene expression profiling of human gonadotrophic pituitary adenoma stem cells - Linhao Yuan; Peiliang Li; Jiang Li; Jiayi Peng; Jianlong Zhouwen; Shunchang Ma; Guijun Jia; Wang Jia; Peng Kang (Acta Neuropathologica Communications, 2023)
Abstract Background Gonadotrophic pituitary adenoma is a major subtype of pituitary adenoma in the sellar region, but it is rarely involved in the hypersecretion of hormones into blood; thus, it is commonly regarded as “non-functioning.” Its tumorigenic mechanisms remain unknown. The aim of this study was to identify human gonadotrophic pituitary adenoma stem cells (hPASCs) and explore the underlying gene expression profiles. In addition, the potential candidate genes involved in the invasive properties of pituitary adenoma were examined. Methods The hPASCs from 14 human gonadotrophic pituitary adenoma clinical samples were cultured and verified via immunohistochemistry. Genetic profiling of hPASCs and the matched tumor cells was performed through RNA-sequencing and subjected to enrichment analysis. By aligning the results with public databases, the candidate genes were screened and examined in invasive and non-invasive gonadotrophic pituitary adenomas using Real-time polymerase chain reaction. Results The hPASCs were successfully isolated and cultured from gonadotrophic pituitary adenoma in vitro, which were identified as positive for generic stem cell markers (Sox2, Oct4, Nestin and CD133) via immunohistochemical staining. The hPASCs could differentiate into the tumor cells expressing follicle-stimulating hormone in the presence of fetal bovine serum in the culture medium. Through RNA-sequencing, 1352 differentially expressed genes were screened and identified significantly enriched in various gene ontologies and important pathways. The expression levels of ANXA2, PMAIP1, SPRY2, C2CD4A, APOD, FGF14 and FKBP10 were significantly upregulated while FNDC5 and MAP3K4 were downregulated in the invasive gonadotrophic pituitary adenomas compared to the non-invasive ones. Conclusion Genetic profiling of hPASCs may explain the tumorigenesis and invasiveness of gonadotrophic pituitary adenoma. ANXA2 may serve as a potential therapeutic target for the treatment of gonadotrophic pituitary adenoma.